Zakres odpowiedzialności pracodawców wobec rodzin pracowników w Drugiej Rzeczypospolitej - Grata, Paweł (Annales. Etyka w Życiu Gospodarczym, 2016)
The aim of this article is the presentation of the range of responsibility of employerstowards workers’ families in Poland in the interwar period. The article also showshow these duties were realised. This problem appeared in Europe with the developmentof a social insurance programme and labour law. The Second Republic of Polandbuilt its own law system for employees’ families. It included health insurance andbenefits, families’ pensions and funeral allowances. Certain obligations were also imposedon employers in the context of labour law. The most important was the obligationto open nursery schools for children of women who worked in factories.